Artificial Intelligence : A Guide to Intelligent Systems - Negnevitsky, Michael (New Delhi Pearson, 2008)
Exploring artificial intelligence, this book covers topics like neural networks and robotics. It examines the range of problems which have been and remain to be solved using Artificial Intelligence tools and techniques.
Include Glossary, Index and Index
Keywords: Artificial intelligence